2010
DOI: 10.3382/japr.2009-00084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of probiotic administration by feed or water on growth parameters of broilers reared on medicated and nonmedicated diets

Abstract: Two separate performance trials were conducted to determine the effects of postpelleting feed or drinking water application of a Lactobacillus-based probiotic, alone or in combination with a phytogenic product, on growth parameters of broilers fed medicated or nonmedicated diets. Trial 1 consisted of 1,000 straight-run broilers that were randomized, placed in floor rearing pens, and fed medicated diets. At the conclusion of the experiment, BW of broilers receiving the probiotic were not different (P > 0.05) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 22 publications
4
25
0
4
Order By: Relevance
“…+ Enterococcus faecium + Bifadobacterium bifidum + Aspergillus oryza) in hens during the late laying period. Eckert et al (2010) reported that body weight and FCR were improved in response to Lactobacillus-based probiotics. Similarly, Zhu et al (2009) reported that Lactobacillus salivarius improved body weight gain and FCR.…”
Section: Modes Of Action Of Probioticsmentioning
confidence: 97%
“…+ Enterococcus faecium + Bifadobacterium bifidum + Aspergillus oryza) in hens during the late laying period. Eckert et al (2010) reported that body weight and FCR were improved in response to Lactobacillus-based probiotics. Similarly, Zhu et al (2009) reported that Lactobacillus salivarius improved body weight gain and FCR.…”
Section: Modes Of Action Of Probioticsmentioning
confidence: 97%
“…Eimeria species are unlike other protozoan parasites in that the primary target tissue is the intestinal epithelium, which results in considerable impairment of growth and feed utilization in poultry. Probiotics may provide a potential alternative to the prophylactic use of drugs in food animals due to their studied abilities to reduce enteric diseases in poultry (Patterson and Burkholder, 2003;Eckert et al, 2010). This study aimed to evaluate the effects of a multispecies, host-specific probiotic product containing Enterococcus, Bifidobacterium, and Lactobacillus species in the feed and water on performance parameters and resistance to coccidiosis (Eimeria infection) in commercial broiler chickens.…”
mentioning
confidence: 99%
“…We anticipate that S. bovis would be able to establish itself in the ceca of poultry and ferment available nutrients and limit colonization of the poultry gastrointestinal tract by Salmonella spp. Probiotic microorganisms may be administered either directly or through feed or water (Eckert et al, 2010). Further research is needed to select a prebiotic substrate to be administered with the S. bovis, to develop an effective delivery system, and evaluate shelf life and stability of the synbiotic system.…”
Section: Discussionmentioning
confidence: 99%